Pentingnya Peran Orang Tua Terhadap Pendidikan Anak - A.Nur Afiat; Nurmia Nurmia; Besse Syukroni Baso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This socialization or community service aims to provide knowledge to the community about the importance of the role of parents in children's education. Through this socialization, it is hoped that the community will pay more attention to their children's education, not depending on the teacher alone, but rather on collaboration between the teacher and the child's parents. The method used in this socialization is a discussion method where there is someone as a presenter and there is someone in the audience who asks questions and is answered by the presenter. The results of observations carried out by researchers in Mattirotasi village showed that parents did not contribute enough to their children's education, which had an impact on learning motivation and also the quality of children's education in Mattirotasi village. The impact of the lack of parental contribution can be seen from the large number of children whose cognitive level does not match the child's own age or educational level, there are still many children who behave negatively towards their friends, for example hitting and making fun of their classmates.